Inflammation, lipids and aortic intima‐media thickness in newborns following chorioamnionitis. (29th April 2016) - Rafferty, Anthony R.; McGrory, Lorraine; Cheung, Michael; Rogerson, Sheryle; Ziannino, Diana; Pyman, Jan; Davis, Peter G.; Burgner, David
Abstract: Aim: This study investigated whether chorioamnionitis was associated with increased inflammation, dyslipidaemia and adverse cardiovascular phenotypes in the immediate postnatal period. Methods: This prospective case–control study included preterm infants (30 +0 –35 +6 weeks gestational age, GA) whose mothers did not have pregnancy‐related conditions that may influence outcomes. Chorioamnionitis was diagnosed by placental histology, and infants were divided retrospectively into cases (chorioamnionitis‐exposed) and controls (unexposed). Serum high‐sensitivity C‐reactive protein (hsCRP), lipid profile, far‐wall abdominal aortic intima‐media thickness (aIMT) and blood pressure (BP) were measured in the first week of life. Results: There were 20 (16 male, mean GA 32.4 weeks) cases and 31 (12 male, mean GA 32.6 weeks) controls. Histological chorioamnionitis was associated with a significant increase in hsCRP and a non‐significant trend towards an adverse lipid profile. There was no evidence of differences in aIMT or BP. Conclusion: Preterm infants exposed to chorioamnionitis have greater postnatal inflammation. There were no early postnatal differences in aIMT or BP. The inflammatory stimulus of chorioamnionitis late in gestation may be of insufficient intensity and duration to result in immediate postnatal alterations to arterial structure. Cardiovascular follow‐up of infants exposed to chorioamnionitis may identify differential risk trajectories and subsequent inflammatory responses.